CMR in inflammatory vasculitis - Raman Subha V; Aneja Ashish; Jarjour Wael N (Journal of Cardiovascular Magnetic Resonance, 2012)
Abstract Vasculitis, the inflammation of blood vessels, can produce devastating complications such as blindness, renal failure, aortic rupture and heart failure through a variety of end-organ effects. Noninvasive imaging with cardiovascular magnetic resonance (CMR) has contributed to improved and earlier diagnosis. CMR may also be used in serial evaluation of such patients as a marker of treatment response and as an indicator of subsequent complications. Unique strengths of CMR favoring its use in such conditions are its abilities to noninvasively visualize both lumen and vessel wall with high resolution. This case-based review focuses on the large- and medium-vessel vasculitides where MR angiography has the greatest utility. Because of increasing recognition of cardiac involvement in small-vessel vasculitides, this review also presents evidence supporting greater consideration of CMR to detect and quantify myocardial microvascular disease. CMR’s complementary role amidst traditional clinical, serological and other diagnostic techniques in personalized care for patients with vasculitis is emphasized. Specifically, the CMR laboratory can address questions related to extent and severity of vascular involvement. As ongoing basic and translational studies better elucidate poorly-defined underlying molecular mechanisms, this review concludes with a discussion of potential directions for the development of more targeted imaging approaches.